2005
DOI: 10.1007/s00702-005-0399-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bilateral Stn-stimulation on psychiatric symptoms and psychosocial functioning in patients with Parkinson’s disease

Abstract: Deep brain stimulation of the subthalamic nucleus is an effective treatment for advanced Parkinson's disease. There is some evidence that subthalamic stimulation not only affects motor function, but also mood, behaviour and cognition. In the present study we investigated the effects of subthalamic stimulation on psychiatric symptoms and psychosocial functioning in a consecutive series of patients with Parkinson's disease. 33 patients were assessed three times prior to surgery and at three, nine weeks as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 55 publications
1
33
0
1
Order By: Relevance
“…"On" state evaluation was considered in studies reporting "on" versus "off" state comparison. In partial duplicates with patients overlapping but with different assessment scales, 39,53 follow-up time 20,31 or comparison groups, 77 a selection of relevant data was performed for each one, and only specific duplicated information was excluded.…”
Section: Methodsmentioning
confidence: 99%
“…"On" state evaluation was considered in studies reporting "on" versus "off" state comparison. In partial duplicates with patients overlapping but with different assessment scales, 39,53 follow-up time 20,31 or comparison groups, 77 a selection of relevant data was performed for each one, and only specific duplicated information was excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Deep brain stimulation (DBS) is often used as a late therapeutic option in the treatment of PD when motor symptoms can not be adequately controlled with medication alone [39]. In addition to improving motor function, some studies have also found DBS to be associated with improvements in mood and depression [40,41,42]. The results of these studies are equivocal, however, as some reports have demonstrated adverse reactions, including significant worsening of depressive symptoms and suicidal ideation [41,43,44] and inducement of mania [45,46,47].…”
Section: Depression and Parkinson's Diseasementioning
confidence: 99%
“…It is also important to note that even for patients with depression of a hypothesized neurochemical etiology, addressing the behavioral and cognitive sequale of this phenomenon can prove helpful [40].…”
Section: Use Of Cbt To Target Specific Symptoms Of Dpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using patient-report inventories have reported improvement in depressive symptomatology. 16,38,74,75 Similarly, studies disagree as to whether apathy does or does not increase after STN DBS. 55,76 On the one hand, studies reporting post-operative incidence of behavioural changes typically do not report a change from the pre-operative state, leaving it possible that the incidence of psychiatric conditions actually improves from pre-operative levels.…”
Section: Controversymentioning
confidence: 99%